ANALYSIS OF COMPLIANCE WITH THE USE OF PERSONAL PROTECTIVE EQUIPMENT (PPE) AMONG HIGH WORKERS ACCORDING TO HEALTH BELIEF MODEL THEORY - Raihan Alhafizh Anugrah Illahi; Luqman Effendi; Dihartawan; Dadang Herdiansyah (Muhammadiyah International Public Health and Medicine Proceeding, 2024)
Several studies were conducted in the United States as well. An incident that occurred in the United States affected workers with a percentage of 85% of people examined who fell, due to not using the prescribed personal protective equipment. 70% of all fall incidents are due to lack of use of personal protective equipment. Employees in the construction industry who do not wear personal protection equipment have a threefold increased risk of getting hurt. to examine how personal protective equipment is used by high-altitude workers in the apartment complex known as The Savyavasa Luxury Residence. This study employs a cross-sectional methodology and is quantitative in nature. Seventy respondents participated in this study. According to the study's findings, 42 (60%) of the employees behaved compliantly when wearing PPE. Cues to action (0.043), perceived advantages (0.00), perceived susceptibility (P=0.005), perceived severity (0.001), self-efficacy (0.007), knowledge factors (P=0.000), and variables unrelated to the obstacle variable (0.808). The conclusion that can be drawn is that almost all variables from the health belief model can predict compliance behavior in using personal protective equipment Companies can conduct outreach regarding PPE about the advantages and disadvantages of not using PPE. Give more attention to new workers regarding compliance with the use of PPE.